2011
DOI: 10.1051/0004-6361/201116491
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters of pre-main sequence stars in open clusters

Abstract: Aims. The aims are twofold: we search and analyse pre-main sequence (PMS) stars in Galactic young open clusters (YOCs) to determine the ages, masses, and spatial distribution of PMS members in YOCs, and to check and compare the performances of different model isochrones. Methods. We compare UBVRI photometric observations to theoretical isochrones in the photometric diagrams. The comparison simultaneously provides membership assignments for both main sequence (MS) and PMS stars and estimates for the physical pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
4
17
0
Order By: Relevance
“…They argue that NGC 3293 is the cluster with the most convincing evidence for a strong deficit of low-mass stars. Delgado et al (2011) also arrived at a similar conclusion from their optical photometry study, which suggested that the mass function is considerably flatter than the Salpeter slope below 2.5 M .…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…They argue that NGC 3293 is the cluster with the most convincing evidence for a strong deficit of low-mass stars. Delgado et al (2011) also arrived at a similar conclusion from their optical photometry study, which suggested that the mass function is considerably flatter than the Salpeter slope below 2.5 M .…”
Section: Introductionsupporting
confidence: 57%
“…This will also provide an important clarification about the previous claims of a significant deficit of low-mass stars in NGC 3293 that were made in some optical photometric studies (Slawson et al 2007;Delgado et al 2011). Our aim here is to determine the number of stars in the [1 − 2] M mass range.…”
Section: Size Of the Low-mass Population And The Mass Function Of Ngcmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed Johnson V magnitude and B − V colour are adopted from Delgado et al (2011). The colour excess E(B − V) was determined by comparison with synthetic photometry from the Atlas9 flux.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for member selection has been described and applied to a sample of 11 southern clusters by Delgado et al (2007Delgado et al ( , 2011hereafter DAYI, DAYII). A spectroscopic assessment of this method for selecting photometric candidate members is now possible for NGC 3293, the only cluster in our sample which is also included in the observations of the Gaia-ESO Spectroscopic Survey (GES).…”
Section: Introductionmentioning
confidence: 99%